Pregnancy-Associated Glycoprotein Level in Early Pregnancy Detection with Prediction of Fetal Number and Gender in Iraqi Local Ewes - AO Al-Rawi, Mohammed; O Hussain ‎, Souhayla (The Iraqi Journal of Veterinary Medicine, 2024)
Early pregnancy detection is an important tool in successful reproductive management in ewes. The objective of this study was to estimate the concentration of serum pregnancy-associated glycoprotein (PAG) during gestation using sheep ELISA kit in order to early distinguish between pregnant and non-pregnant ewes and the possible association with litter size, and fetal gender. Estrus was synchronized and blood samples were collected at day 0 (day of mating), 18, 30, 60, and 120 after mating from 18 Iraqi cross breed synchronized ewes. The result of PAG level (ng/ml) during estrus has shown insignificant difference between G1(CIDR group), G2(vaginal sponge group) and G3 (control group), while at day 18, 30, 60 and 120 of pregnancy was significantly (p˂0.05) higher in G1 and G2, in comparison with G3. The discrimination value (cutoff point) for detection of pregnancy by PAG test was ˃ 0.915 ng/ ml (using ROC Curve) and based on breeding data from day 18 PAG values were detectable in all pregnant ewes. It was also proved that mean values were significantly (P˂0.05) higher in twin than single pregnancies and significantly (P˂0.05) higher in male single than female single pregnancy in crossbred Iraqi ewes according to the data collected from day 0 to the end of pregnancy and follow the pregnancy up to the day of birth. Altogether, it is concluded that, ovine pregnancy may be reliably detected with fetal number and gender from day 18 after mating onward by using sheep ELISA kit of pregnancy associated glycoprotein‎‎‎.